Análise e caracterização de superfície de cavidades de molde de injeção utilizado e recondicionado para a fabricação de pontas de Gutta-Percha - Ferreira, Lucas Homem Grossi (Universidade Federal de São Carlos, 2023)
The success of a dental procedure, regarding root canal treatment processes (Endodontics), is directly related to the filling material that will serve as a substitute for the tooth root tissue. The dental material widely used for this function is known as Gutta-Percha (GP) cones. This polymer is extracted naturally from trees in the Malay Peninsula and Indonesia, industrially polymerized and mixed with organic and inorganic compounds. The process by injection molds is one of the manufacturing processes of GP conical points and there is evidence of a scarcity of literature with coverage in the subject. About the injection process, the polymer chains of the injected material tend to be typically oriented in the direction of the injection flow and suffer constant interference due to the friction between the injected polymeric material and the mold surface. Thus, friction is related to the characteristics of the injected polymer and aspects of roughness of the mold surface, the study aims to investigate the influence on the length reach of GP points during the injection process in two different roughness profiles. In this work, the surface characteristics of injection mold were evaluated by correlating the roughness of the mold cavities with the length reach of GP points before and after mold surface treatment. After modification of the cavity roughness profile, the surfaces showed an increase in their irregularities presenting roughness parameters, in μm, for Ra (0.30 - 0.75), Rq (0.56 - 1.68), Rt (3.43 - 20.97), Rz (2.51 - 8.76), Rp (1.73 - 16.30) and Rc (1.72 - 10.03) resulting in a reduction of point length up to 27%. It is concluded that surfaces with roughness profiles with higher peaks and greater distances between peaks and valleys negatively influence the filling of GP cones in the mold cavities.
Surface analysis and assessment of recycled injection mold used on Gutta Percha cones manufacturing
Keywords: Gutta-Percha; Processo de injeção; Perfil de rugosidade; Superfície molde de injeção; Condições superficiais; Injection process; Roughness profile; Injection mold surface; Surface conditions; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO